Анна Каренина: [роман] / Лев Толстой - Толстой Лев Николаевич (Мировая классика, 2020)
Экземпляры: ЦБ (20230413) / Инвентарный номер: 56373 / Цена: 150.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 53 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44